VD_FINDINFO HC / 2010 / 46 vom 28. Oktober 2009 - VD Tribunal cantonal (2009)
DIVORCE, OBLIGATION D'ENTRETIEN, CONJOINT, ÉTAT DE SANTÉ, REVENU HYPOTHÉTIQUE | 125 CC, 138 al. 1 CC, 342 al. 2 CPC, 452 al. 1ter CPC, 452 al. 2 CPC